2021
DOI: 10.3389/fnhum.2021.630813
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Beta Power Reflects Attentional Top-Down Modulation After Psychosocial Stress Induction

Abstract: Selective attention depends on goal-directed and stimulus-driven modulatory factors, each relayed by different brain rhythms. Under certain circumstances, stress-related states can change the balance between goal-directed and stimulus-driven factors. However, the neuronal mechanisms underlying these changes remain unclear. In this study, we explored how psychosocial stress can modulate brain rhythms during an attentional task and a task-free period. We recorded the EEG and ECG activity of 42 healthy participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…Previous studies reported that cortisol secretion is related to EEG wakefulness alertness in humans [37]. Another study reported that the increase of beta band power might reflect top-down attentional modulation after a stress-induced environment [38]. Therefore, we believed that the increased mental stress possibility enhances brain alertness as a consequence.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies reported that cortisol secretion is related to EEG wakefulness alertness in humans [37]. Another study reported that the increase of beta band power might reflect top-down attentional modulation after a stress-induced environment [38]. Therefore, we believed that the increased mental stress possibility enhances brain alertness as a consequence.…”
Section: Discussionmentioning
confidence: 80%
“…The EEG beta power is known to be highly correlated with the cortisol hormone level in the body, which increases in response to stress [57]. Moreover, beta power is known to be an indicator of attention, concentration, and anxiety [42,58]. Numerous studies selected the power increase of the beta waves to identify stress [59][60][61][62] and the power decrease of the beta waves to identify mental fatigue and drowsiness [63][64][65].…”
Section: Results Of Eeg Signals On a Driving Simulatormentioning
confidence: 99%
“…Some studies used the help of other bio-sensors to categorize and label the acquired EEG signals [33,34] (again, we point out the importance of a precise time alignment between different sensors); some other studies relied on the drivers' selfreport [35]; other studies classified the mental activity using an arbitrary threshold on the EEG signal level and labeling the categories on the basis of threshold trespassing [36]. In this study, we adopted the analysis of the beta activities to identify the stress in drivers from the acquired EEG signals, and this method is well known in the literature [39][40][41][42]. Few studies have designed and developed EEG sensors with various architectures.…”
Section: Introductionmentioning
confidence: 99%
“…These two frequency bands, theta and beta, have been reported as the key observable indices for clinical effects of tDCS treatment related to major symptoms of PTSD, such as stress, depressive and anxiety. According to Palacios-García's study, the increase in psychosocial stress and stress-related anxiety was related to specific changes in beta-band ( 38 ). Dunkley also reported theta band plays a critical role in attentional, depressive and anxiety-related sequelae observed in PTSD populations ( 39 ).…”
Section: Discussionmentioning
confidence: 99%